How Well do Existing Indices Measure the Strength of the East Asian Winter Monsoon - 王林 陈文 (Advances in atmospheric sciences, 2010)
Defining the intensity of the East Asian winter monsoon （EAWM） with a simple index has been a difficult task. This paper elaborates on the meanings of 18 existing EAWM strength indices and classifies them into four categories： low level wind indices, upper zonal wind shear indices, east-west pressure contrast indices, and East Asian trough indices. The temporal/spatial performance and prediction potential of these indices are then analyzed for the 1957-2001 period. It reveals that on the decadal timescale, most indices except the east-west pressure contrast indices can well capture the continuous weakening of the EAWM around 1986. On the interannual timescale, the low level wind indices and East Asian trough indices have the best predictability based on knowledge of the El Nio-Southern Oscillation and Arctic Oscillation, respectively. All the 18 existing indices can well describe the EAWM-related circulation, precipitation, and lower tropospheric air temperature anomalies. However, the variations of surface air temperature over large areas of central China cannot be well captured by most indices, which is possibly related to topographic effects. The results of this study may provide a possible reference for future studies of the EAWM.